Effects of a similar amount of regular non-structured or competitive physical activity across late adulthood: a cross-sectional study - Palumbo, M.; Modena, R.; Bortolan, L.; Skafidas, S.; Callovini, A.; Savoldelli, A.; Gilli, F.; Fornasiero, A.; Schena, F.; Pellegrini, B.; Zoppirolli, C. (Frontiers in Sports and Active Living, 2024)
Introduction: Master athletes are examples of successful aging. It is not clear whether it is the competitive-oriented training or just the amount of total regular exercise that reduces the age-related decline in physiological functions. We aimed to compare health-related parameters in competitive (C) and physically active older adults (A) that performed the same weekly physical activity (PA) amount.Methods: 17 C and 17 A were matched for age (8 and 9 male participants under and over 70 years old respectively, for both groups) and weekly PA amount (GPAQ). Body composition, leg and arm maximal strength, balance and reaction time were measured; moreover, leg and arm exercise efficiency, estimated VO2max, and VO2/HR relationships were evaluated. Perception of life and sleep quality was also assessed through specific questionnaires (SF-36 and PSQI). The effect of group (C vs A), age (U70 vs O70) and their interaction was examined through a Two-Way ANOVA test.Results: C dedicated more time to vigorous PA compared to A (p = 0.03), while less to moderate daily work (p < 0.01) and active commuting (p = 0.06). C exhibited better body composition (all p < 0.05), higher leg maximal strength (p <0.05) and a trend for elevated arm strength (p = 0.06). Reaction time, leg and arm cycling efficiency were similar in the two groups (all p > 0.05), while balance reduced in A O70. Estimated VO2max was higher for C in leg cycling (p = 0.05) and remained constant across ages (all p > 0.05). VO2/HR relationship, life and sleep quality did not differ for groups and ages.Conclusions: Regular physical exercise of about 6000 METs/week seems to have a beneficial effect on health-related parameters, both in non-structured and competitive PA, when compared to sedentary behaviour. However, the older adults engaged in competitive training exhibit further advantages: better body composition, higher arm and leg muscle strength, and higher leg VO2max. This study highlights the importance of encouraging active lifestyles for maintaining long-term health, high levels of life quality perception and reducing age-related decline. However, vigorous training suitability needs to be verified by a team of PA specialists.